2016
DOI: 10.3938/jkps.68.1439
|View full text |Cite
|
Sign up to set email alerts
|

Giant strain in lead-free relaxor/ferroelectric piezocomposite ceramics

Abstract: The crystal structural, ferroelectric, and electric-field-induced-strain (EFIS) properties of leadfree relaxor/ferroelectric piezocomposites were investigated. The relaxor-matrix phases were mixed with the ferroelectric-seed phases by using a conventional ceramic processing route. The addition of the ferroelectric seed phase dramatically enhanced the EFIS of the relaxor matrix phase at low electric fields. Giant strains of 745 pm/V at 4 kV/mm and 466 pm/V at 3 kV/mm were obtained when the seed contents were 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…We propose that the broadened peaks at higher values of T s in the MWS-derived ceramics may be ascribed to the improvement in density and/or grain size, which contributes to decrease the leakage current and enhances the ferroelectricity. It was also reported that the increased sintering temperature in (Na 0.5 K 0.5 )NbO 3 -based materials can enhance ferroelectricity [39] or rhombohedral symmetry in MWS-derived specimens [16,[23][24][25][26][27][28][29][30][31]. Previous studies on the effect of BaZrO 3 (BZ)-modification on the crystal structure of BNKT ceramics [32] have found that the BZ modification induces a phase transition from rhombohedral to pseudocubic symmetry.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We propose that the broadened peaks at higher values of T s in the MWS-derived ceramics may be ascribed to the improvement in density and/or grain size, which contributes to decrease the leakage current and enhances the ferroelectricity. It was also reported that the increased sintering temperature in (Na 0.5 K 0.5 )NbO 3 -based materials can enhance ferroelectricity [39] or rhombohedral symmetry in MWS-derived specimens [16,[23][24][25][26][27][28][29][30][31]. Previous studies on the effect of BaZrO 3 (BZ)-modification on the crystal structure of BNKT ceramics [32] have found that the BZ modification induces a phase transition from rhombohedral to pseudocubic symmetry.…”
Section: Resultsmentioning
confidence: 99%
“…In this respect, Biperovskite compounds have also attracted much attention as leadfree actuator materials, because of their large strains [16,[23][24][25][26][27][28][29][30][31]. The large strain observed at the normal and relaxor ferroelectric phase boundary was recently found to be closely related to the nanoscale composite of the normal and relaxor ferroelectric phases [30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it was reported that a large normalized strain ( S max / E max ) of about 600 pm/V under a relatively low field (4 kV/mm) was obtained in BNT–ST ceramics of MPB regions 16–19 . This abnormally large strain in BNT‐based (or BNT–ST) ceramics is associated with the reversible electric‐field‐induced phase transition from an ergodic relaxor (ER) to a ferroelectric (FE) 20–24 . Recently, several studies have suggested that exploring ternary systems can result in discovering a high‒performance piezoelectric in BNT–ST ceramics.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19] This abnormally large strain in BNT-based (or BNT-ST) ceramics is associated with the reversible electric-field-induced phase transition from an ergodic relaxor (ER) to a ferroelectric (FE). [20][21][22][23][24] Recently, several studies have suggested that exploring ternary systems can result in discovering a high-performance piezoelectric in BNT-ST ceramics. As a result, a maximum strain of 0.27% at 4 kV/mm for BNT-ST-AgNbO 3 , 25 a high strain of 0.24% with 4 kV/mm at low sintering temperature for BNT-ST-LiNbO 3 , 26 a large strain of 0.239% under ultralow driving field of 3 kV/mm for BNT-ST-KTaO 3 , 24 and so on have been published.…”
Section: Introductionmentioning
confidence: 99%